Theoretical Exploration of the Interference Minimum in Molecular High-Order Harmonic Generation (Journal of Atomic and Molecular Sciences, 2016)
The interference minimum in the molecular high-order harmonic generationis studied by numerically solving the non-Born-Oppenheimer approximationtime-dependent Schrödinger equation. The results show that two kinds of interferenceminima appear in the high-order harmonic spectrum when the hydrogen molecularion is exposed to the laser pulse. Furthermore, by adjusting wavelength of the laser aswell as initial condition of nucleus, it is found that two kinds of interference minimaare ascribed to the molecular structure and the electronic dynamics behavior inducedby the laser field, respectively. Besides, the time-frequency distributions and the electronwave packet distributions are calculated to better understand the mechanism ofthe minimum.